Exploring culture war related attacks on public libraries: results from a pilot study on information activities of the far-right - Fredrik Hanell; Hanna Carlsson; Daniel Ihrmark (Information Research: An International Electronic Journal)
Introduction. This paper reports initial findings from a research project focusing on how information activities of the far-right promoting ideologically motivated pressure and threats against cultural institutions develop, spread and unfold, the logic governing these attacks and how they affect public libraries and librarians.